Kalanchoe ×sampsonii [K. ×hankeyi × K. sexangularis] (Crassulaceae subfam. Kalanchooideae), a horticulturally successful nothospecies from South Africa with enhanced vegetative and reproductive characters - Smith, Gideon F. (Phytotaxa, 2023)
A new, shrubby nothospecies, Kalanchoe ×sampsonii (Crassulaceae subfam. Kalanchooideae) is described from South Africa. The parents of the nothospecies are K. ×hankeyi and K. sexangularis, both of which are included in K. subg. Kalanchoe. When exposed to direct solar irradiation, virtually all vegetative plant parts of K. ×hankeyi, one of the parents of K. ×sampsonii, will be reddish-infused, a character inherited from K. sexangularis, which is also one parent of K. ×hankeyi. This desirable horticultural trait was further enhanced through back-crossing with K. sexangularis. At reproductive maturity, plants of K. ×sampsonii bear large, dense-flowered inflorescences that structurally more closely resemble those of K. longiflora, the other parent of K. ×hankeyi. The flowers of K. ×sampsonii are larger than those of K. sexangularis and the corolla tube and lobes are more intensely yellow than those of both K. ×hankeyi and K. sexangularis.